Організаційно-правові засади становлення та розвитку органів місцевого самоврядування та суб’єктів владних повноважень (XVIII –XX століття) - Мирний, Д. В.; Myrnyi, D. V. (Право і суспільство. - 2021. - № 1, ч. 2. - С. 15-20, 2021)
Доведено, що в досліджуваний період, впроваджувані державно-управлінські аспекти на нормативному рівні характеризувались яскраво-вираженим охоронно-традиціоналістським характером зміцнюючи феодальні підвалини, консерватизмом системи державного управління, неадекватно відображаючи об’єктивні потреби державного та суспільного життя, створюючи передумови для подальшого відставання держави і віддаляючи українське суспільство від західноєвропейських ідей та концепцій у сфері демократизації державного управління.

The scientific article is devoted to the research and complex analysis of organizational and legal bases of formation and development of local selfgovernment bodies and subjects of power (XVIII-XX centuries). Taking into account the doctrinal study, it proved that in the period under study, the implemented public administration aspects at the regulatory level characterized by a pronounced security and traditionalist character, strengthening the feudal foundations, conservatism of public administration, inadequately reflecting the objective needs of state and public life. Further lagging behind the state and distancing Ukrainian society from Western European ideas and concepts in the field of democratization of public administration. In the context of determining the organizational and legal framework for the formation and development of local governments and executive bodies, the fundamental problem of state building was the issue of decentralization of power, which is relevant today and affects a number of important legal postulates, including those underlying the entire regulatory system. , for example, the principles of unity of the system of state power as the foundation of any state. Along with the unity of state power, this issue affects the principles of unity of the system of public authorities, without which it is impossible to legislate, state regulation and management, coordination of the functioning of institutions of representation. It is a special system of balance and harmony in the activities of central government and local, their relationship, as well as the place and role of the judiciary. Emphasis placed on the fact that it is indisputable that the state as a special institution is a holistic mechanism, characterized by the presence of various internally agreed structural elements, where bodies and institutions of public administration occupy the determining role, as well as mechanisms governing operational activities.

Доказано, что в исследуемый период, внедряемые государственно-управленческие аспекты на нормативном уровне характеризовались ярко-выраженным охранно-традиционалистским характером, укрепляя феодальные устои, консерватизмом системы государственного управления, неадекватно отражая объективные потребности государственной и общественной жизни, создавая предпосылки для дальнейшего отставания украинского общества от западноевропейских идей и концепций в сфере демократизации государственного управления.
Organizational and legal principles of establishment and development of local government bodies and authorities of the authority (XVIII-XX century)
Мирний, Д. В. Організаційно-правові засади становлення та розвитку органів місцевого самоврядування та суб’єктів владних повноважень (XVIII –XX століття) / Мирний Д. В. // Право і суспільство. - 2021. - № 1, ч. 2. - С. 15-20. - DOI: https://doi.org/10.32842/2078-3736/2021.1.2.3.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; Україна. Ukraine. Украина; державне управління; governance; государственное управление; історико-правовий аналіз; historical and legal analysis; историко-правовой анализ; організаційно-правові засади; organizational and legal principles; организационно-правовые основы; органи місцевого самоврядування; local governments; органы местного самоуправления; губернії; province; губернии; державний механізм; state mechanism; государственный механизм